2011
DOI: 10.1002/adsc.201100487
|View full text |Cite
|
Sign up to set email alerts
|

User‐Friendly [(Diglyme)NiBr2]‐Catalyzed Direct Alkylations of Heteroarenes with Unactivated Alkyl Halides through CH Bond Cleavages

Abstract: A nitrogen and phosphorus ligand-free catalytic system derived from inexpensive [(di-A C H T U N G T R E N N U N G glyme)NiBr 2 ] allowed for efficient direct C À H bond alkylations of heteroarenes with unactivated b-hydrogen-containing alkyl halides under basic reaction conditions. Keywords: alkylation; azoles; C À H activation; heterocycles; mechanism; nickel Substituted heteroarenes are indispensable substructures of, among others, biologically active compounds and functional materials. [1][2][3] In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 59 publications
1
33
0
2
Order By: Relevance
“…Experiments were run to understand the mechanism of this alkylation and suggested that an alkyl radical intermediate arising from the alkyl halide is produced during the reaction by single-electron transfer from a heteroarylnickelate intermediate (Scheme 19.33). These results were extended shortly thereafter by Ackermann et al [53], who described the alkylation of …”
Section: C-h Alkylation Catalyzed By First-row Transition Metalssupporting
confidence: 50%
“…Experiments were run to understand the mechanism of this alkylation and suggested that an alkyl radical intermediate arising from the alkyl halide is produced during the reaction by single-electron transfer from a heteroarylnickelate intermediate (Scheme 19.33). These results were extended shortly thereafter by Ackermann et al [53], who described the alkylation of …”
Section: C-h Alkylation Catalyzed By First-row Transition Metalssupporting
confidence: 50%
“…(2)]. [121] More recently,t he Punji group reported the synthesis and use of quinoline-based NNNpincer nickel(II) complexes for the direct alkylation of Scheme 34. Nickel/copper-and copper-catalyzed alkylation of azoles with primary and secondary alkyl halides.…”
Section: Alkylation With Alkyl Halidesmentioning
confidence: 99%
“…This last strategy was later on fully exploited by Ackermann for the nickel/copper co‐catalyzed direct alkylation of benzoxazoles and benzothiazoles with primary alkyl halides through the generation of alkyl radicals upon reaction with an azole–nickel(I) intermediate [Scheme , Eq. (2)] . More recently, the Punji group reported the synthesis and use of quinoline‐based NNN‐pincer nickel(II) complexes for the direct alkylation of benzothiazoles and 5‐aryloxazole derivatives with primary alkyl halides …”
Section: Alkylation Of Heteroarenesmentioning
confidence: 99%